S-1 and irinotecan plus bevacizumab versus mFOLFOX6 or CapeOX plus bevacizumab as first-line treatment in patients with metastatic colorectal cancer (TRICOLORE): a randomized, open-label, phase III, noninferiority trial. (27th December 2017) - Yamada, Y; Denda, T; Gamoh, M; Iwanaga, I; Yuki, S; Shimodaira, H; Nakamura, M; Yamaguchi, T; Ohori, H; Kobayashi, K; Tsuda, M; Kobayashi, Y; et al.
Abstract: Background: Combination therapy with oral fluoropyrimidine and irinotecan has not yet been established as first-line treatment of metastatic colorectal cancer (mCRC). We carried out a randomized, open-label, phase III trial to determine whether S-1 and irinotecan plus bevacizumab is noninferior to mFOLFOX6 or CapeOX plus bevacizumab in terms of progression-free survival (PFS). Patients and methods: Patients from 53 institutions who had previously untreated mCRC were randomly assigned (1 : 1) to receive either mFOLFOX6 or CapeOX plus bevacizumab (control group) or S-1 and irinotecan plus bevacizumab (experimental group; a 3-week regimen: intravenous infusions of irinotecan 150 mg/m 2 and bevacizumab 7.5 mg/kg on day 1, oral S-1 80 mg/m 2 twice daily for 2 weeks, followed by a 1-week rest; or a 4-week regimen: irinotecan 100 mg/m 2 and bevacizumab 5 mg/kg on days 1 and 15, S-1 80 mg/m 2 twice daily for 2 weeks, followed by a 2-week rest). The primary end point was PFS. The noninferiority margin was 1.25; noninferiority would be established if the upper limit of the 95% confidence interval (CI) for the hazard ratio (HR) of the control group versus the experimental group was less than this margin. Result: Between June 2012 and September 2014, 487 patients underwent randomization. Two hundred and forty-three patients assigned to the control group and 241 assigned to the experimental group were included in the primary analysis. Median PFS was 10.8 months (95% CI 9.6–11.6) in the control group and 14.0 months (95% CI 12.4–15.5) in the experimental group (HR 0.84, 95% CI 0.70–1.02; P < 0.0001 for noninferiority, P = 0.0815 for superiority). One hundred and fifty-seven patients (64.9%) in the control group and 140 (58.6%) in the experimental group had adverse events of grade 3 or higher. Conclusion: S-1 and irinotecan plus bevacizumab is noninferior to mFOLFOX6 or CapeOX plus bevacizumab with respect to PFS as first-line treatment of mCRC and could be a new standard treatment. Clinical trials number: UMIN000007834